PENERAPAN MANAJEMEN PADA DIRI MAHASISWA DALAM PENDIDIKAN ISLAM - Rusma Permana (STIT Al-Marhalah Al-Ulya Bekasi, 2021)
ABSRACTSelf management means putting everything on a regular basis in life, in the use of time, choice, interests, activities, as well as in the physical and mental balance. It also means pushing self to get ahead, arrange all the elements of the personal, controlling potential willingness to accomplish good things, and develop various aspects of private life to make it more perfect. The first requirement for all students to achieve their education goals is self-motivation. Secondly, self organization is setting up as well as possible against the thought, effort, time, places, objects and all other resources in one's life so that students achieved personal efficiency. So that his dual role as students and workers can go hand in hand. From recognition of the informant about the students apply learning strategies in regards to qualify themselves indicate that there are a number of students who are aware of a good self management will bring a profit for them. Among them, the Division of time between lectures and other activities are not interrupted, his schedule became organized, as students and other activities are not disrupted, could set out the lesson, as well as being able to tackle the problems facing it. Keywords: Self Management, Students, Multiple Roles